Polymerase Slippage at Vesicular Stomatitis Virus Gene Junctions To Generate Poly(A) Is Regulated by the Upstream 3′-AUAC-5′ Tetranucleotide: Implications for the Mechanism of Transcription Termination - Barr, John N. (American Society for Microbiology, 2001)
Termination of mRNA synthesis in vesicular stomatitis virus (VSV), the prototypic rhabdovirus, is controlled by a 13-nucleotide gene end sequence which comprises the conserved tetranucleotide 3′-AUAC-5′, the U(7) tract and the intergenic dinucleotide. mRNAs terminated at this sequence possess 100- to 300-nucleotide-long 3′ poly(A) tails which are thought to result from polymerase slippage (reiterative transcription) by the VSV polymerase on the U(7) tract. Previously we determined that in addition to the AUAC tetranucleotide, the U(7) tract was an essential signal in the termination process. Shortening or interrupting the U(7) tract abolished termination. These altered U tracts also prevented the polymerase from performing reiterative transcription necessary for generation of the mRNA poly(A) tail and thus established seven residues as the minimum length of U tract that allowed reiterative transcription to occur. In this study we investigated whether sequences other than the essential U(7) tract are involved in controlling polymerase slippage. We investigated whether the AUAC tetranucleotide affected the process of reiterative transcription by analyzing the nucleotide sequence of RNAs transcribed from altered subgenomic templates and infectious VSV variants. The tetranucleotide was found to regulate reiterative transcription on the U(7) tract. The extent of polymerase slippage was governed not by specific tetranucleotide sequences but rather by nucleotide composition such that slippage occurred when the tetranucleotide was composed of A or U residues but not when it was composed of G or C residues. This suggested that polymerase slippage was controlled, at least in part, by the strength of base pairing between the template and nascent strands. Further data presented here indicate that the tetranucleotide contains both a signal that directs the VSV polymerase to slip on the downstream U(7) tract and also a signal that directs a slipping polymerase to terminate mRNA synthesis.